Framing the Syrian Uprising: Comparative Analysis of Khaleej Times and The New York Times - Bakht Rawan, Ph.D, Shahid Imran (JSSH, 2023)
The study reports on framing of the Syrian uprising by two international newspapers i.e. Khaleej Times and The New York Times in the perspectives of their respective cultures, political inclinations and national policies regarding the problem in question.